Establishing a pulmonary rehabilitation programme in primary care in Greece: A FRESH AIR implementation study. (15th November 2019) - Anastasaki, Marilena; Trigoni, Maria; Pantouvaki, Anna; Trouli, Marianna; Mavrogianni, Maria; Chavannes, Niels; Pooler, Jillian; van Kampen, Sanne; Jones, Rupert; Lionis, Christos; Tsiligianni, Ioanna
Pulmonary rehabilitation (PR) is an evidence-based, low-cost, non-medical treatment approach for patients with chronic respiratory diseases. This study aimed to start and assess the feasibility, acceptability and impact of a PR programme on health and quality of life of respiratory patients, for the first time in primary care in Crete, Greece and, particularly, in a low-resource rural setting. This was an implementation study with before–after outcome evaluation and qualitative interviews with patients and stakeholders. In a rural primary healthcare centre, patients with chronic obstructive pulmonary disease (COPD) and/or asthma were recruited. The implementation strategy included adaptation of a PR programme previously developed in United Kingdom and Uganda and training of clinical staff in programme delivery. The intervention comprised of 6 weeks of exercise and education sessions, supervised by physiotherapists, nurse and general practitioner. Patient outcomes (Clinical COPD Questionnaire (CCQ), COPD Assessment Test (CAT), St. George's Respiratory Questionnaire (SGRQ), Patient Health Questionnaire-9 (PHQ-9), Incremental Shuttle Walking Test (ISWT)) were analysed descriptively. Qualitative outcomes (feasibility, acceptability) were analysed using thematic content analysis. With minor adaptations to the original programme, 40 patients initiated (24 with COPD and 16 with asthma) and 31 completed PR (19 with COPD and 12 with asthma). Clinically important improvements in all outcomes were documented (mean differences (95% CIs) for CCQ: −0.53 (−0.81, −0.24), CAT: −5.93 (−8.27, −3.60), SGRQ: −23.00 (−29.42, −16.58), PHQ-9: −1.10 (−2.32, 0.12), ISWT: 87.39 (59.37, 115.40)). The direct PR benefits and the necessity of implementing similar initiatives in remote areas were highlighted. This study provided evidence about the multiple impacts of a PR programme, indicating that it could be both feasible and acceptable in low-resource, primary care settings.